Holding on to Clarity: Reconciling the Federal Kidnapping Statute with the Trafficking Victims Protection Act - Reese, Benjamin (2015)
In recent decades, the international community has come to recognize human trafficking as a problem of epidemic proportions. Congress responded to this global crisis in 2000 by passing the Trafficking Victims Protection Act (TVPA) and has since supplemented that comprehensive enactment. But, in light of the widespread use of psychological rather than physical coercion in trafficking cases, a long-standing split among federal courts regarding the scope of the federal kidnapping statute raises significant concerns about the United States’ efforts to combat traffickers. In particular, the broad interpretation adopted by several circuits threatens effective enforcement of statutes designed to prosecute traffickers, endangers the due process rights of potential defendants, and risks rendering the criminal provisions of the TVPA superfluous. This Note argues that those broader interpretations are incorrect as a matter of proper statutory interpretation, and especially when considered in light of the passage of the TVPA. It further contends that, in kidnapping-by-deception cases, the prosecution must demonstrate that the defendant intended to back up the deception with force or the threat of force if his ruse failed